Development process of the preconception education booklet - Nurunniyah, Siti; Nurdiati, Detty Siti; Julia, Madarina; Hadi, Hamam (International Journal of Research in Medical Sciences, 2021)
Background: Healthy preconception is very essential to prepare for pregnancy, childbirth, and healthy babies. However, many women still lack of knowledge on having healthy preconceptions. Effective education requires relevant and standardized material and educational media. The objective of this study aimed to explain the process of developing a preconception education booklet. Methods: We have developed a preconception education booklet. The method to develop this booklet involved five main stages: literature review, interviews with preconception women and health care workers in primary health care, focus group discussions with the lecturer of midwifery, nutrition, and health promotion, expert review, and measure response test from women of reproductive age. Results: Our literature review has come out with a summary of the preconception educational materials consist of 15 topics that have been present. By using In-depth interviews, we observed and then developed materials that were required by women of reproductive age and health workers and they consisted of 10 topics. Our Focus Group Discussion has come out with the need to grouping the materials into 4 groups (pillars). We then validated our booklet material by using Expert review. Finally, our response test showed that 96% of respondents agree that booklet material is easy to understand, 90% of respondents agree that booklets are interesting to read, 93% of respondents agree that booklet material is relevant to their condition, 90% of respondents agree that the material in the booklet is the material it needs, 86% of respondents agree that the material in this booklet can help with their health problems, 80% of respondents agree that the choice of words in the booklet is easy to understand, 90% of respondents agree that the cover of the booklet is very interesting, 100 respondents agree that the font of the letters in the booklet is easy to read, 80% of respondents agreed that the illustrations relevant with the materials. Booklets were positively appreciated by 87% (26 out of 30 respondents) of reproductive-age women. Conclusions: Our preconception booklet can be used by health care workers to provide pregnancy preparation counselling for women of reproductive age.